Effect of physical exercises and perceived stress interaction on students' satisfaction with life - V.O. Olefir; M.A. Kuznetsov; V.V. Plokhikh (H.S. Skovoroda Kharkov National Pedagogical University, 2019)
Purpose : to find out the effect of regular physical exercises and perceived stress interaction on students' satisfaction with life. Material and methods : The study involved university students (n = 355; М age = 19,97; SD = 2,12). The moderator analysis was conducted according to the cross-sectional questionnaire. Results : It is determined that the difference in students' satisfaction with life at the average and high perceived stress is due to physical exercises. The influence of the interaction of variables (physical activity x perceived stress) on satisfaction with life was statistically significant. Conclusions : It is revealed the peculiarities of interaction between the physical exercises and perceived stress. The reduce of satisfaction with life under the influence of perceived stress is more typical for those students who do not regularly practice physical exercises. Physical exercises act as a buffer against stress.